ANALISA KEKUATAN RANGKA DUDUKAN CYLINDER HIDROLIK - Firmansyah, Doni Bagus (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2019)
Abstract - The basic elements of the scissor mechanism & structure can be used to make a lot of modelling of structure and function of the motion. Scissor lift mechanism was considered more powerful and secure than pulley mechanisms of imposition. From this research, it is known that there is failure of the cylinder holder frame structure which causes the occurrence of deflection and on beam. The methods used in this study is static analysis to find out the distribution of Von Misses Stress on design/modelling until getting the Factor of Safety. The results of this research are obtained the quantities of the maximum factor of safety 1,65 with a maximum stress of the material 151,8 N/mm2 and the yield point of the material is 250 N/mm2. The conclusions of the results show that the material used is safe because the standard factor of safety for static load above 1 and the material design used is still meet the safety factors.